Cardiac Output Assessment in Patients Supported with Left Ventricular Assist Device: Discordance Between Thermodilution and Indirect Fick Cardiac Output Measurements. Issue 4 (July 2017) - Tehrani, David M.; Grinstein, Jonathan; Kalantari, Sara; Kim, Gene; Sarswat, Nitasha; Adatya, Sirtaz; Sayer, Gabriel; Uriel, Nir
Abstract : Cardiac output (CO) assessed by thermodilution (TD) and indirect Fick (iFK) methods is commonly employed in left ventricular assist device (LVAD) patients; however, no study has assessed agreement. This study assesses correlation between these methods and association with hemodynamic/echocardiographic data in LVAD patients. Discordance was defined as a 20% difference between TD and iFK CO measurements. Bias and agreement were determined via the Bland–Altman technique in both the overall sample and iFK-stratified tertiles. Correlation with each assessment of CO and right heart catheterization (RHC) hemodynamics was performed. Among 111 RHCs, the mean CO for TD and iFK were 4.65 ± 1.33 (range: 1.44–9.30) and 5.37 ± 1.51 (range: 3.07–11.80) L/min ( p < 0.001), respectively, with a calculated discordance of 45.9%. A correlation coefficient of 0.66 with a bias of −0.72 L/min was found. The lower and upper limit of precision were −3.12 and 1.68 L/min, respectively. By tertile analysis, bias (lower and upper limit of precision) for the low, middle, and high tertile groups were −0.24 (−1.88 and 1.40), −0.48 (−2.50 and 1.53), and −1.39 (−4.18 and 1.39) L/min, respectively. No significant correlation was found between either method with right atrial pressure or pulmonary capillary wedge pressure or any valvular condition. Substantial discrepancies exist between TD and iFK CO in LVAD patients. Although fixed bias was small, the limits of agreement extend into the clinically relevant area, with larger bias being present at higher CO. Studies with flow probes are needed to define which method better represents CO in LVAD patients.